PENERAPAN MODEL EXPERIENTIAL LEARNING UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Bahasa Indonesia Kelas VIII SMP Negeri 5 Lahat) - Rusmilawati Rusmilawati (UNIB Press, 2020)
This study aims to describe the application of experiential learning models in class VIII of SMP Negeri 5 Lahat. The method used in this study is a combined research method (mixed method research) which is a combination of action research and action research. The research subjects are students of SMP Negeri 5 Lahat in the first semester of 2019/2020 school year. The number of students for the class ptk 32 people, for the experiment 31 people, and for the control class 30 people. Data collection methods in this study use the assessment sheet and test results. Data analysis using score analysis and test tests consisting of different test between cycles difference test of two unrelated samples. The results showed that the application of the experimental learning model could increase responsibility and learning achievement in Indonesian VIII grade subjects at SMP Negeri 5 Lahat.